Tanggung Gugat Penyelenggara Jalan terhadap Kecelakaan Lalu Lintas Akibat Jalan Rusak : Studi Hukum Perdata - , Faradila Faradila; Nur Arifudin; Nomensen Freddy Siahaan (Pusat Riset dan Inovasi Nasional, 2026)
This is related to the rights of traffic accident victims regulated in Article 240 of Law 22 of 2009 concerning Road Traffic and Transportation